1994
DOI: 10.1177/0734242x9401200503
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Collection Systems in European Cities

Abstract: A 1989 survey compares the conceptual and technical approaches to the collection of municipal solid waste, secondary materials and household hazardous wastes in eight major European cities. The collection systems reflect local structural conditions as well as the different political tasks of municipal waste management. The traditional focus on collection and treatment has been enlarged by separate collection and public education, and economic considerations are of increasing importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Figure 1a shows the composition of HSW in terms of use type (packaging/putrescible/others). It can be seen that package waste only constitutes 17.5%, which is rather modest compared to the 40% contribution in HSW in American cities like Tucson, Arizona, Milwaukee (Wisconsin) and Marin County (California), studied by Rathje and his team (Rathje et al 1985), and to the 33% contribution of packaging materials to HSW reported for Vienna (Scharff & Vogel 1994). These results support the explanation provided above with regards to consumption patterns in developed countries as opposed to those in developing countries.…”
Section: Compositionmentioning
confidence: 88%
“…Figure 1a shows the composition of HSW in terms of use type (packaging/putrescible/others). It can be seen that package waste only constitutes 17.5%, which is rather modest compared to the 40% contribution in HSW in American cities like Tucson, Arizona, Milwaukee (Wisconsin) and Marin County (California), studied by Rathje and his team (Rathje et al 1985), and to the 33% contribution of packaging materials to HSW reported for Vienna (Scharff & Vogel 1994). These results support the explanation provided above with regards to consumption patterns in developed countries as opposed to those in developing countries.…”
Section: Compositionmentioning
confidence: 88%
“…GNI capita −1 can satisfactorily predict the percentage recovered by the formal sector (r = 0.92, p < 10 −7 , R adj 2 = 0.84). Official statistics from 1990 show that municipal waste recycling rates in the EU ranged from 1 to 20%, with half of the 12 member states having rates between <1 -6% (ERL, 1992) is corroborated by a 1989 survey of 8 European cities: the seven Western European cities had recycling rates in the range of 5-20% (Scharff and Vogel, 1994). During the past 10-20 years, high-income countries have been rediscovering the benefits and advantages of both materials recycling and organic recovery as an integral part of their waste (and resource) management systems, and have invested heavily in both physical infrastructure and communication strategies, increasing public participation in separate collection schemes, and overall recycling rates to current levels of 40% or more.…”
Section: Resource Managementmentioning
confidence: 97%
“…Likewise, Scharff & Vogel (1994) carried out a comparative study of waste collection systems in eight of the most important European capitals that shows how the particular characteristics of each city and the different administrative management policies are the main causes of the differences between the systems employed.…”
Section: Recycling Behaviourmentioning
confidence: 99%